Putative lung adenocarcinoma with epidermal growth factor receptor mutation presenting as carcinoma of unknown primary site: A case report. Issue 7 (February 2018) - Yamasaki, Masahiro; Funaishi, Kunihiko; Saito, Naomi; Sakano, Ayaka; Fujihara, Megumu; Daido, Wakako; Ishiyama, Sayaka; Deguchi, Naoko; Taniwaki, Masaya; Ohashi, Nobuyuki; Hattori, Noboru
Abstract: Rationale: Only a few cases of putative lung adenocarcinoma presenting as carcinoma of unknown primary site (CUP) with epidermal growth factor receptor (EGFR) mutation have been reported, and the efficacy of EGFR-tyrosine kinase inhibitors (TKIs) for these cases is unclear. Patient concerns and diagnoses: A 67-year-old man complained of paresis of the right lower extremity, dysarthria, and memory disturbance. Computed tomography and magnetic resonance imaging showed multiple brain tumors with brain edema and swelling of the left supraclavicular, mediastinal, and upper abdominal lymph nodes. Moreover, a metastatic duodenal tumor was detected via upper gastrointestinal endoscopy examination. The biopsy specimen of the lesion was examined and was diagnosed as adenocarcinoma with CK7 and TTF-1 positivity. Finally, the case was diagnosed as EGFR mutation-positive putative lung adenocarcinoma presenting as CUP. Interventions and outcomes: Oral erlotinib, an EGFR-TKI, was administered at 150 mg daily. Five weeks later, the brain lesions and several swollen lymph nodes showed marked improvement, and the symptoms of the patient also improved. Three months later, the duodenal lesion was undetected on upper gastrointestinal endoscopy. After an 8-month follow-up, the patient was well with no disease progression. Lessons: Putative lung adenocarcinoma presenting as CUP may have EGFR mutation, and EGFR-TKI therapy may be effective for such malignancy.